ANALISIS PENJUALAN JILBAB JASMINE MELALUI LIVE STREAMING DAN FLASH SALE - Nur Afifah Eka Mayrawanti; Dhyah Wulansari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The hijab industry in Indonesia is experiencing a very rapid growth rate, a phenomenon driven by the increasing number of Muslim women and the development of hijab fashion trends that continue to transform in line with social and cultural dynamics. Jasmine Hijab, as one of the leading hijab brands in Indonesia, utilizes digital marketing strategies as the main instrument to boost sales, with the implementation of techniques such as live streaming and flash sale which are an integral part of their approach. This research targets to oversee an in-depth research of the efficacy of live streaming and flash sale techniques on Jasmine Hijab sales through a qualitative approach. The outcome of this examination reveal that there is a compelling diversity in efficacy between live streaming and flash sale in increasing Jasmine Hijab sales. The benefaction of this survey is in the deeper understanding of how digital marketing strategies influence hijab sales in Indonesia, seen from the customer perspective.